Implementation of the Lokananta Records Surakarta Virtual Museum as a Promotional and Educational Media - Taufiqurrakhman Nur Hidayat; Fendi Aji Purnomo; Aoron Sulistyono; Ovide Decroly Wisnu Ardhi; Yudho Yudhanto (Universitas Sebelas Maret, 2023)
Abstract : A museum is a non-profit institution tin the service of society and its development, open to the public, which acquires, conserves, researches, communicates and exhibits both tangible and intangible heritage of humanity and its environment for the purposes of education, study and enjoyment. A virtual museum is a digital entity that refers to the characteristics of a museum, in order to enhance or add to the experience of a museum through interactivity, richness of content and personalization. The creation of a virtual museum from the Lokananta Records Surakarta museum is needed as an effort to improve and add to the experience of the Lokananta Records Surakarta museum. The Lokananta Records Surakarta virtual museum application has been successfully developed as a virtual museum with the feature of being able to explore the virtual museum, interact with 3-dimensional objects in it such as vinyl record, cassette tape, videotape, compact disc and the Lokananta Records Surakarta Production Process Tool Collection.Abstrak : Museum adalah lembaga nirlaba yang melayani masyarakat dan perkembangannya, terbuka untuk umum, yang memperoleh, melestarikan, meneliti, mengkomunikasikan, dan memamerkan warisan manusia dan lingkungannya baik yang berwujud maupun yang tidak berwujud untuk tujuan pendidikan, studi, pendidikan dan hiburan. Museum virtual adalah entitas digital yang mengacu pada karakteristik museum, untuk meningkatkan atau menambah pengalaman museum melalui interaktivitas, kekayaan konten, dan personalisasi. Pembuatan virtual museum dari museum Lokananta Records Surakarta diperlukan sebagai upaya untuk meningkatkan dan menambah pengalaman museum Lokananta Records Surakarta.Penelitian ini berfokus pada pengembangan museum virtual untuk merepresentasikan Lokananta Records Surakarta. Desain aplikasi mengikuti siklus hidup pengembangan multimedia.Aplikasi museum virtual Lokananta Records Surakarta telah berhasil dikembangkan sebagai museum virtual dengan fitur dapat menjelajahi museum virtual, berinteraksi dengan objek 3 dimensi di dalamnya seperti piringan hitam, kaset, kaset video, compact disc dan Lokananta Mencatat Koleksi Alat Proses Produksi Surakarta.